Effect of Zinc Additive and Annealing on Dielectric Characteristics of the PSCCO Compound - mahdi, shatha hashim; F. Hamady, Naba; Akbar, Demiral (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The ceramic PSCCO (PbSr2Ca2Cu3O) and (PbSr2Ca2Cu2.4Zn0.6O) compounds were prepared using high-purity oxides (x=0 and0.6%) via solid reaction. The samples were then pressed into tablets with 1.5 cm diameter, at 5.4MPa for two minutes and sintered at 850°C for 24 hours. AFM was used to study the surface structure. It showed a stable improvement in the crystallization of the model surfaces. As a result of the chemical reaction between the raw materials, the granules united with each other, increasing their size. At a frequency range of 50-106 Hz, regarding the dielectric properties, including the dielectric constant, and dielectric loss factor, at room temperature, it measured electrical conductivity and electrical resistance as a function of frequency in the range from 50 to106 Hz, Measurements of the ceramic composite model PSCCO (PbSr2Ca2Cu3O) plus (PbSr2Ca2Cu2.4 Zn0.6O) showed dielectric constant (11.23 and 10.30), while also measuring the loss angle shadow and alternating conductivity. The following parameters were measured for two models at a frequency range of 50-106 Hz: dielectric loss factor (7.76 and 9.45), tangent loss tangent (tanδ) (0.69 and 0.91), and alternating electrical conductivity (σa.c). The dielectric constant values for both models were 11.23 and 12.43. The insulating properties showed good stability with temperature within the range of room temperature to 200°C.and 13.71 for the base compound PbSr2Ca2Cu3O, at different temperatures, the dielectric constant of compound PbSr2Ca2Cu2.4Zn0.6O was measured to be 10.3, 11.15, and 12.06, indicating its potential use at high temperatures.